2020
DOI: 10.1101/2020.04.27.064881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell resolution analysis of the crosstalk between chemogenically activated astrocytes and microglia

Abstract: 25Astrocytes are the most common glial cell type in the brain, yet, it is still not clear how their 26activation affects the transcriptome of other brain cells such as microglia and neurons. 27Engineered G protein-coupled receptors called Designer Receptors Exclusively Activated by 28Designer Drugs (DREADDS) make it possible to selectively activate specific cell types, such as 29 neurons and astrocytes. By combining the selective activation of astrocytes with single cell RNA 30 sequencing, we were able to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…Clearly, there is an urgent need for new and improved actuators that allow precise control over astrocytes’ spatial and temporal dynamics and specific signaling pathways. Thorough characterization, including transcriptomic and proteomic profiling, will be necessary to develop a mechanistic understanding of precisely how their activation influences astrocytes, neural circuits, and animal behavior, either directly or indirectly ( Figueiredo et al, 2014 ; Octeau et al, 2019 ; Philtjens et al, 2021 ; Yu et al, 2020 ). Such experiments should also consider how the observed effects depend on stimulation parameters and the approach itself (e.g., light-induced heating-mediated effects; Courtney et al, 2021 ; Owen et al, 2019 ; Schmidt & Oheim, 2020 ).…”
Section: Measuring Manipulating and Targeting Astrocyte Functionsmentioning
confidence: 99%
“…Clearly, there is an urgent need for new and improved actuators that allow precise control over astrocytes’ spatial and temporal dynamics and specific signaling pathways. Thorough characterization, including transcriptomic and proteomic profiling, will be necessary to develop a mechanistic understanding of precisely how their activation influences astrocytes, neural circuits, and animal behavior, either directly or indirectly ( Figueiredo et al, 2014 ; Octeau et al, 2019 ; Philtjens et al, 2021 ; Yu et al, 2020 ). Such experiments should also consider how the observed effects depend on stimulation parameters and the approach itself (e.g., light-induced heating-mediated effects; Courtney et al, 2021 ; Owen et al, 2019 ; Schmidt & Oheim, 2020 ).…”
Section: Measuring Manipulating and Targeting Astrocyte Functionsmentioning
confidence: 99%
“…Chronic DREADD activation of astrocytes has been shown to induce transcriptomic changes in adjacent microglia, notably with the upregulation of a set of Alzheimer’s disease-associated genes that are associated to a microglial phenotype which is protective against AD pathology 31,32 . Our results extend this finding by showing that, functionally, the result of chronic astrocytic DREADD stimulation is associated to an increase in microglial density and especially in a microglial phenotype that more efficiently responds to and limits AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review reveals that only a handful of studies (unbiasedly) unveiled the transcriptomic/proteomic profile upon chemogenetic activation, as summarized in Table 2 . These studies focused on CNO-induced DREADD modulation of neurons [ 24 , 81 , 82 , 83 , 84 , 85 ] or astrocytes [ 86 , 87 , 88 ], and reported corresponding molecular effects on the neurons [ 24 , 81 , 82 , 84 ] or astrocytes [ 86 , 87 , 89 ] themselves, and/or on neighboring endothelial cells [ 85 ] or microglia [ 87 ]. Briefly, studies depicting neuronal alterations exclusively related to DREADD activation, reported an activity-dependent upregulation of several genes in the BDNF-TrkB signaling pathway [ 81 , 82 ] or an upregulation of multiple immediately early genes, JUNB interaction partners and a possible involvement of PKA signaling pathway [ 84 ].…”
Section: Dreaddful Opportunitiesmentioning
confidence: 99%
“…Briefly, studies depicting neuronal alterations exclusively related to DREADD activation, reported an activity-dependent upregulation of several genes in the BDNF-TrkB signaling pathway [ 81 , 82 ] or an upregulation of multiple immediately early genes, JUNB interaction partners and a possible involvement of PKA signaling pathway [ 84 ]. Similarly, studies focusing on the astrocytic alterations described altered signaling pathways associated with neuroinflammatory responses [ 89 ], GPCR signaling [ 87 ], and calcium ion homeostasis [ 87 ] or biological functions related to immune responses, regulation of transcription, and translation and cell proliferation/growth [ 89 ]. Moreover, astrocytic activation also led to an upregulation of Thbs1 , which is involved in synapse formation and function [ 86 , 89 ].…”
Section: Dreaddful Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation